ГЛОБАЛЛАШУВ ШАРОИТИДА МИЛЛИЙ ТАЪЛИМГА ХОРИЖ ТАЖРИБАЛАРИ ИНТЕГРАЦИЯСИНИНГ ҚИЁСИЙ ТАҲЛИЛИ - Турумбетова, З. (SCIENCE and SOCIETY, 2021)
The article provides a comparative analysis of the best practices of higher education in developed countries and reflects the issues of integration into the education system of our country. It also analyzes the activities of students, advisors, facilitators and supervisors in the organization of independent creative work of students.